Radical prostatectomy on YouTube: education or disinformation? - Siegel, Fabian; Kuru, Timur H.; Boehm, Katharina; Leitsmann, Marianne; Probst, Kai Alexander; Struck, Julian P.; Huber, Johannes; Borgmann, Hendrik; Salem, Johannes (Archivos españoles de urología, 2023)
Background: YouTube is the second most popular website worldwide. It features numerous videos about radical prostatectomy. The aim of this study was to assess the quality of these videos and screen their benefit for patients and doctors. Methods: All videos on YouTube about radical prostatectomy were analysed using a specially developed software (python 2.7, numpy). According to a predefined selection process most relevant videos were analyzed for quality and reliability using Suitability Assessment of Materials (SAM)-Score, Global Quality Score and others. Results: Out of 3520 search results, 179 videos were selected and analysed. Videos were watched a median of 5836 times (interquartile range (IQR): 11945.5; 18-721546). The median duration was 7.2 minutes (min). 125 of the videos were about robotic prostatectomy. 69 videos each were directly addressed to patients and doctors. Medical content generally was of low quality, while technical quality and total quality were at a high level. Reliability was good. Conclusions: Videos on radical prostatectomy on YouTube allow for patient information. While technical quality and reliability are classified as acceptable, medical content was low and warranted preselection. In contrast to Loeb et al.we did not observe a negative correlation between number of views and scientific quality in different scores. Our findings support the need for preselection of videos on YouTube as the potential benefit may vary between videos with the significant risk of low medical quality.
Gesehen am 08.10.2024